Influência do lantânio nas propriedades estruturais do SrSnO3 - Cassia-santos, M. R.; Mendes, S. B.; Gurgel, M. F. C.; Figueiredo, A. T.; Godinho Jr., M.; Braz, C. E. M. [UNESP]; Longo, E. [UNESP] (Associação Brasileira de Cerâmica, 2014)
The tin compounds with perovskite structure have shown promising properties for use as electronic ceramics such as sensors, catalysts and most recently, photoluminescent materials. In this work the effect of lanthanum on the structural properties of La xSr1-xSnO3 and the evaluation of this system as photoluminescent material were studied. The La xSr1-xSnO3 powders were synthesized by the polymeric precursor method and thermal treatments at 600, 800 and 1000 ºC for 4 h. The systems were characterized by thermal analysis, X-ray diffraction, specific surface area measurements, UV-Visible spectroscopy, infrared spectroscopy, scanning electron microscopy and photoluminescence measurements. X-ray diffraction analysis shows crystalline phase with cubic perovskite structure, as a function of calcination temperature for the additions of lanthanum (1, 5 and 10 mol%). Despite the addition of lanthanum in SrSnO3, the perovskite structure is stable. The crystallite size decreased with the addition of lanthanum, indicating that this dopant may be acting as a possible particle growth inhibitor and hence decreasing crystallite size. The results of the specific surface area show that the addition of lanthanum favors, in general, the formation of higher surface area solids. Values of the optical gap, according to the theory of Tauc, are between 3.81 and 3.98 eV, showing a gradual increase due to the addition of lanthanum. The powders doped with 1 mol% of lanthanum and treated at 600 ºC presented higher photoluminescent emission intensity.

Os estanatos com estrutura perovskita têm apresentado propriedades promissoras à sua utilização como cerâmica eletrônica do tipo: sensores, catalisadores e mais recentemente, fotoluminescente. Neste trabalho foi analisado o estudo do efeito do lantânio nas propriedades estruturais do estanato de estrôncio e a avaliação como sistema fotoluminescente. Os pós de La xSr1-xSnO3 foram sintetizados pelo método do precursor polimérico e tratados termicamente a 600, 800 e 1000 ºC por 4 h. Os sistemas foram caracterizados por análise térmica, difração de raios X, análise de área de superfície específica, espectroscopia no UV-Visível, no infravermelho, microscopia eletrônica de varredura e medidas fotoluminescentes. A partir dos resultados de difração de raios X observa-se a formação de um sistema cristalino monofásico com estrutura perovskita cúbica, tanto em função da temperatura de calcinação como para as adições de lantânio (1, 5 e 10% em mol). Apesar da adição de lantânio no SrSnO3, a estrutura perovskita se mantém estável. O tamanho de cristalito diminui com a adição de lantânio, o que indica que o lantânio pode estar agindo como possível inibidor de crescimento de partícula e, conseqüentemente, diminuindo o tamanho de cristalito. Os resultados de área de superfície especifica mostram que a adição de lantânio favorece, de forma geral, a formação de sólidos com maior área. Os valores de gap óptico obtidos pela teoria de Tauc estão entre 3,81 e 3,98 eV, apresentando um aumento gradativo em função da adição de lantânio. Os pós tratados a 600 ºC com 1% em mol de lantânio são os que apresentam maior intensidade de emissão fotoluminescente.
The influence of lanthanum on the structural properties of SrSnO3
Keywords: estanatos; perovskita; lantânio; fotoluminescência; stannates; perovskite; lanthanum; photoluminescence